Developing An E-Learning Platform For Islamic Education That Incorporates The Principles Of Religious Moderation Within School Settings - Saeful Anam; Nur Mubin (SYAMIL: Journal of Islamic Education, 2023)
The establishment of online Islamic religious e-learning with a focus on religious moderation in educational institutions is an endeavor aimed at broadening the availability of well-rounded and balanced Islamic religious education through digital learning platforms. This research aimed to create an e-learning system that specifically emphasizes the principles of religious moderation within schools. The research adopted a developmental approach (R&D), by utilizing the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). After conducting an analysis, the e-learning system was designed and developed using cutting-edge technology that enables active student interaction and engagement. Subsequently, the e-learning system was introduced as a pilot project in the school setting. Students and teachers actively participated in utilizing this system to access Islamic religious content that was customized to their individual needs and comprehension level. Throughout the implementation phase, an assessment was conducted to evaluate the effectiveness of the e-learning system in enhancing comprehension of the Islamic faith and fostering a moderate religious mindset. The findings of this research demonstrated a significant demand for Islamic religious education focused on religious moderation. There was a pressing need for the development of efficient learning tools to facilitate successful comprehension of Islamic Studies materials, particularly among junior high school students. This conclusion is supported by the analysis of data using the Wilcoxon test, which yielded a t-value of -4.878 and a p-value of 0.00, indicating statistical significance (p < 0.05).